CURRENT ISSUES AND NEW METHODS IN COMPARATIVE LINGUISTICS - Avazova Lobar Buriyevna; Bobojonova Felura Shuhrat qizi (Modern American Journals, 2025)
This research explores the current issues and innovative methods in comparative linguistics. The study focuses on the theoretical and methodological foundations of comparing different language systems, highlighting the challenges faced by modern linguists in identifying universal and language-specific features. It also examines the role of digital technologies, corpus linguistics, and artificial intelligence in advancing comparative linguistic analysis. The findings emphasize the importance of interdisciplinary approaches and the integration of modern computational tools in linguistic research to achieve more precise and objective results.
Keywords: Comparative linguistics, linguistic typology, modern methods, digital technologies, corpus linguistics, artificial intelligence, language comparison.